ON THE IMORTANCE OF EXPROPRIATION IN THE ROMAN EMPIRE AND IN MODERN EUROPE - Franz-Rudolf Herber (European Scientific Journal, ESJ, 2015)
The question, whether there was expropriation in the Roman Empire or not, is difficult to answer, because the ancient texts do reveal only very small evidence of public Roman law. A textbook on public law of the Roman Empire unfortunately is not known. Let us, therefore, make the following thought experiment: How would be our understanding ofRoman private law, if Justinian1 would not have bequeath such a great collection of private law to us? Our knowledge of Roman private law would then be very fragmentary, to recognize cross-correlations would be almost impossible. The scientific approach to expropriation for infrastructure projects of the state has to start from the following conisderations:“Public interest“ respectively “general welfare“ is as a legal term ubiquitous in Roman history: In the proper name “res publica Romana“, which goes back to the beginnings of Rome, occurs the commitment of the Roman society to the principles of public interest and of public welfare. In the introductory text of Iustinian's >Digests